2010
DOI: 10.1158/1541-7786.mcr-09-0472
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibits the Proliferation and Invasion of Pancreatic Cancer Cells through Degradation of Insulin Receptor Substrate-1 Protein

Abstract: Nitric oxide (NO), which plays a role in the posttranslational modification of proteins, exhibits tumoricidal activity. However, the mechanism remains largely unclear. We investigated whether the regulation of insulin receptor substrate (IRS)-1 protein expression and insulin/insulin-like growth factor (IGF) signaling by NO is involved in the proliferation and invasion of pancreatic cancer cells. NO donor inhibited insulin/IGF-I-stimulated phosphorylation of insulin receptor/IGF-I receptor, IRS-1, Akt/PKB, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…NO inhibits IGF-IR and EGFR activity, as reported previously (29,30). Furthermore, NO induces the degradation of IRS-1 protein and the phosphorylation of IRS-1 (14,29,30). In addition, Yasukawa et al reported that NO directly modifies Akt protein and inhibits its activity (11).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…NO inhibits IGF-IR and EGFR activity, as reported previously (29,30). Furthermore, NO induces the degradation of IRS-1 protein and the phosphorylation of IRS-1 (14,29,30). In addition, Yasukawa et al reported that NO directly modifies Akt protein and inhibits its activity (11).…”
Section: Discussionsupporting
confidence: 55%
“…In addition, Yasukawa et al reported that NO directly modifies Akt protein and inhibits its activity (11). Recent studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing research showed that NO donors were effective on various malignant tumors, such as myeloma, breast cancer, ovarian cancer, prostate cancer and pancreatic cancer (15)(16)(17). Moreover, it is worth noting that more and more NO-donor hybrids have been designed, synthesized and evaluated as antitumor agents (Table 1), which will be discussed in the following part of this review.…”
Section: No-donor Hybrid Compounds As Anti-cancer Agentsmentioning
confidence: 99%